On the Question of Inter-Slavonic Language Contacts in the 15–17th centuries (on the material of the diplomatic correspondence of Muscovy) - Гарбуль, Людмила Павловна Павловна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The present article deals with inter-Slavonic language contacts, in particular, language contacts between the East Slavic and West Slavic languages on the lexical level on the material of diplomatic correspondence of Muscovy. The publication examines anew exposed lexical (vyobraziti ‘list, adduce; mention, refer(to); describe’, zapomogati ‘support’, nedoroslyj ‘very young; under age, juvenile, minor’) and semantic (uznati ‘admit; agree, concede’) inter-Slavonic borrowings. Moreover, the article deals with the role of the written language of the Great Duchy of Lithuania in Polish-Russian language contacts.
Keywords: inter-Slavonic language contacts, Polish-Russian language contacts, diplomatic correspondence (documents), the written language of the Great Duchy of Lithuania, lexical borrowing, semantic borrowing/calque